Why Was Asia Resilient? : Lessons from the Past and for the Future - Jeasakul, Phakawa; Lim, Cheng; Lundback, Erik. (Washington, D.C. : International Monetary Fund, 2014)
Asia proved to be remarkably resilient in the face of the global financial crisis, but why was its output performance stronger than that of other regions? The paper shows that better initial conditions-in the form of lower external and financial vulnerabilities-contributed significantly to Asia's resilience. Key pre-crisis factors included moderate credit expansion, reliance on deposit funding, enhanced bank asset quality, reduced external financing, and improved current accounts. These improvements reflected the lessons from the Asian financial crisis in the late 1990s, which helped reshape both public policies and private sector behavior. For example, several countries stepped up their use of macroprudential policies, well before they were recognized as an essential component of the financial stability toolkit. They also overhauled financial regulations and strengthened oversight of financial institutions, which helped reduce risk-taking by households and firms before the global financial crisis. Looking ahead, Asia is in the process of adjusting to more volatile external conditions and higher risk premiums. By drawing the right lessons from its pre-crisis experiences, Asia's economies will be better equipped to address new risks associated with increased cross-border capital flows and greater integration with the rest of the world.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet